Coexistence Performance of High-Altitude Platform and Terrestrial Systems Using Gigabit Communication Links to Serve Specialist Users. (19th August 2008) - Peng, Z.; Grace, D.
Abstract : This paper presents three feasible methods to serve specialist users within a service area of up to 150 km diameter by using spot-beam gigabit wireless communication links from high-altitude platforms (HAPs). A single HAP serving multiple spot beams coexists with terrestrial systems, all sharing a common frequency band. The schemes provided in the paper are used to adjust the pointing direction of aperture antennas operating in the mm-wave bands, such that the peak carrier to interference plus noise ratio (CINR) is delivered directly toward the location of the specialist users; the schemes include the small step size scheme, half distance scheme, and beam switch scheme. The pointing process is controlled iteratively using the mean distance between the peak CINR locations and user positions. The paper shows that both the small step size and half distance schemes significantly enhance the CINR at the user, but performance is further improved if beams with adverse performance below a specific threshold are switched off, or are assigned another channel.